Ionic liquid mediated four-component synthesis of novel phthalazinone based indole-pyran hybrids as cytotoxic agents - M. Shaheer Malik (Elsevier, 2022)
A robust design and synthesis of novel phthalazinone based indole-pyran hybrids as cytotoxic agents is described. A relatively safer ionic liquid medium ([BMIM]BF4) was utilized to mediate a one-pot, four-component reaction to access the novel hybrids in short reaction time and good yields. The cytotoxic potential of the hybrids was investigated against selected cancer cell lines. The hybrids 5h and 5b displayed potent activity with IC50 values in the range of 5.8–9.6 μM. The insilico docking demonstrated a pronounced affinity of hybrids 5h and 5b towards the human tankyrase-1 enzyme exhibiting binding energies values of −11.2 and −10.2 kcal/mole, respectively. Additional ADME and drug likeliness analyses revealed the potential of the active hybrids to be taken forward for advanced studies.